Masalah yang kerap muncul Implementasi dari metode Enhanced Recovery after Caesarean Surgery - Rizal, Raisha Rahmani; Redy Bintang Pratama; Luthfi, Ahmad Angga (CV. Jasa Sukses Abadi, 2024)
The problem that often arises in post sectio caesarea (SC) patients is fear of mobilizing earlier because of pain. Approximately 60% of patients have very severe pain, 25% moderate pain and 15% mild pain. The SC ERACS method is claimed to reduce postoperative pain, and allows for a faster recovery process. Enhanced recovery after caesarean surgery (ERACS) is a concept that combines evidence-based aspects of perioperative care to accelerate patient recovery. This standardizes perioperative management and achieves reproducible improvements in quality of care. Early studies on the ERACS protocol performed in colorectal surgery reported reduced hospital stays, hospitalizations, and postoperative complications coupled with improved patient satisfaction. The specific components of the ERACS protocol differ between surgical specialties and institutions, but the core principles remain the same. These principles involve interventions spanning the preoperative, intraoperative, and postoperative periods. It addresses common reasons that delay patient recovery from surgery and prolong hospital stay such as inadequate analgesia, slow return of bowel function, and delayed ambulation. Some are slower. In the study conducted, 84 patients were found using the ERACS method with a distribution of 42 people in each group. Length of Stay with an average of 6 days and 11 days respectively. This study aims to make a critical review to find out whether the application of the ERACS method can provide improvements to the length of stay in the hospital, postoperative mobilization time, return of bowel/digestive tract function, and pain free condition.